Building Green Trust Through Brand Image: A Study on Dietinfood Consumers from Millennial and Gen Z Segments - Silaban, Sonia Artha Ria; Komaladewi, Rita (Integrated Journal of Business and Economics (IJBE), 2025)
This study aims to analyze the influence of green marketing elements, which include green product, green price, green place, and green promotion, on green trust through green brand image among healthy food consumers from the Generation Millennial and Generation Z cohorts. The sample of this study consisted of 210 Dietinfood customers in Purwakarta who fall into the the Generation Millennial and Generation Z categories. This research employed a quantitative approach using primary data collected through questionnaire distribution. The data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results indicate that green product, green price, green place, and green promotion significantly influence green brand image. However, only green product, green promotion, and green brand image have a direct effect on green trust. Moreover, green brand image is proven to mediate the influence of green product, green price, and green place on green trust among healthy food consumers from the Millennial and Gen Z groups. The implications of this study suggest that Dietinfood is perceived positively by consumers in terms of its commitment to sustainability. Therefore, the company should consistently maintain and enhance its environmentally friendly marketing practices in order to strengthen consumer trust and brand competitiveness in the growing healthy food market.